Cicero’s concept of natural law and the political system of the principate of the Roman state - Arlauskas, Saulius (Politologija, 1999)
In this short study, the author, save using Cicero’s concept of the Natural Law, tries to derive inside the determinants concerning the birth of the political system of the principate of the Roman State. Cicero’s ideas help figure out that, owing to the consolidation of aristocratic and democratic rudiments in the structure of the Roman state sparkled by given historical constellations, a specifically Roman legal concept of justice and natural law is formed. Forced by its influence as if programmed, the republican political system evolves in the direction of the model of Principate. In this study, an effort is opened to authenticate that emperor Augustus obeys the demands of both political forces (populars and optimates) but in the process of implementing this given "programme". Therefore, the study contends that in the outcome, the emperor conciliates the objectives of the political forces (which are controversial) and erects such an institution of supreme authority which, in addition to becoming an instrument that consolidates the society, in the forthcoming history of the Roman state serves as a progressive element. Cicero’s concept of natural law determines that democratic, aristocratic, and monarchical status was integrated into the legal consciousness of the Romans. Save using Cicero’s concept of natural law, subsequent analysis of the political programmes of the optimates (aristocratic party) and the populars (democratic party) revealed that on the eve of Caesar’s dictatorship, the Roman society at large was ready to vote for a monarchy-type of government based upon the pattern of the political system of principate. It was determined in this way that the principate of Emperor Augustus had emerged in a regular manner. The latter conclusion enables us to solve the endless historiographical discussions related to the origin of Augustus’ principate in favor of those who support the defenders of a teleological point of view.